Problem-Based Learning through Reading, Questioning, and Answering (PBLRQA): A Teaching Module to Improve Critical Thinking and Science Communication Skills in High School Students - Louto, Fadlun Fadilawati; Mohammad Jamhari; Achmad Ramadhan (Jurnal Penelitian dan Pengembangan Pendidikan, 2025)
Students' ability to identify problems in the PBL syntax is still weak, which affects their critical thinking and communication skills. This has become an issue that requires a solution. This study aims to develop a PBLRQA teaching module to improve senior high school students’ critical thinking and scientific communication skills. The type of research used is R&D (Research and Development) with a 4D development model. The research subjects were 30 tenth-grade students from class X9. The instruments used included validation sheets, essay questions to assess critical thinking skills, and observation sheets to assess communication skills. Data analysis was conducted using percentage formulas and the N-gain test. The results showed a significant difference in the average scores of students’ critical thinking skills before and after the treatment. The average pretest score was 11.3, and after the treatment using the PBLRQA teaching module, the average posttest score increased to 85.16. The N-gain score was 0.83, categorized as high, indicating that the PBLRQA teaching module was effective. The conclusion of this study is that the PBLRQA teaching module has been proven effective in improving students’ critical thinking and scientific communication skills. The implication of this research is that the developed PBLRQA teaching module can be used as a learning tool in biology classes, particularly for the topic of viruses.